Identification of Parents' Perceptions of Antibiotic Use for Individualized Community Education - Lauren Havens BSN, RN, CEN; Misty Schwartz PhD, RN (SAGE Publishing, 2016)
The purpose of this project was to evaluate parents' perceptions of antibiotics to better understand the barriers related to judicious antibiotic use and for selection of educational resources. A descriptive survey design was distributed electronically to a convenience sample of parents in Omaha, Nebraska, using the Parental Perception on Antibiotics scale. A total of 170 completed surveys were evaluated. Nearly all parents (97%) disagreed with the statement "antibiotics are needed for the common cold," and 90% were in agreement that antibiotics treat bacterial infections. Respondents did not expect an antibiotic after being seen for the common cold. All reported they "never" changed doctors when antibiotics were not prescribed. The parents completing this survey were knowledgeable about antibiotic use. Results demonstrate implications for both education efforts and patient-provider interactions. This project supports the need for community-specific identification of parents' perceptions for individualized education and promotion of proper antibiotic use.